Effectiveness of Telemedicine to Improve Drug Taking Adherence in Tuberculosis Patients: Meta-Analysis - Rahayuningsih, Lilik Anggar Sri; Tamtomo, Didik; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Tuberculosis is a disease caused by a bacterium called Mycobacterium tuberculosis which usually attacks the lungs, but TB bacteria can attack any part of the body such as the kidneys, spine and brain. TB treatment must be carried out regularly so that it can be declared cured so it is necessary to monitor the patient's medication intake, namely by using telemedicine. This study aims to analyze the effectiveness of the use of telemedicine in tuberculosis patients to increase treatment adherence. Subjects and Method: Meta-analysis was carried out using PICO as follows: The population in this study was tuberculosis patients. Intervention in the form of the use of telemedicine. Comparison is not using telemedicine. The outcome is an increase in medication adherence. A meta-analytic study was applied to this study with electronic data sources: Google Scholar, MEDLINE/PubMed, Science Direct and web of science. The article used is a full-text article with a Randomized Control Trial (RCT) study design. There are 6 articles used in this study which were analyzed using the Review Manager 5.3 application. Results: A total of 6 articles with Randomized Control Trial (RCT) studies from Malaysia, Peru, Cameroon, China and Ethiopia showed that the use of telemedicine is effective for increasing treatment adherence in tuberculosis patients, and the effect is statistically significant (aOR = 1.98; 95% CI = 1.53 to 2.55; p<0.001).Conclusion: The use of telemedicine is effective in increasing medication adherence in tuberculosis patients. Keywords: telemedicine, tuberculosis, medication adherence Correspondence: Lilik Anggar Sri Rahayuningsih. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36A, Surakarta 57126, Central Java, Indonesia. Email: lilikanggar@gmail.com Mobile: +6285647587323